Hemelipoglycoprotein from the ornate sheep tick, Dermacentor marginatus: structural and functional characterization - Štěrbová, Jarmila (Jihočeská univerzita, 2011)
The main aim of this study is the biochemical characterization of a carrier protein from the ornate sheep tick Dermacentor marginatus, hemelipoglycoprotein, with emphasis on its size in native conditions, its glycosylation and identification of its modifying glycans, and examining its carbohydrate-binding specificity.
Hemelipoglycoprotein from the ornate sheep tick, Dermacentor marginatus: structural and functional characterization
Keywords: hemelipoclycoprotein; tick; Dermacentor marginatus; sugar-binding protein; hemelipoclycoprotein; tick; Dermacentor marginatus; sugar-binding protein